Prevalence of adverse events during ticagrelor versus clopidogrel treatment and its association with premature discontinuation of dual antiplatelet therapy in East Asian patients with acute coronary syndrome - Kang, Min Gyu; Ahn, Jong Hwa; Kim, Kyehwan; Koh, Jin-Sin; Park, Joeng Rang; Hwang, Seok Jae; Park, Yongwhi; Tantry, Udaya S.; Gurbel, Paul A.; Hwang, Jin-Yong; Jeong, Young-Hoon (Frontiers in Cardiovascular Medicine, 2022)
Background: Clinical evidence raises the issues regarding the high risk of adverse events and serious bleeding in East Asian patients receiving standard-dose ticagrelor treatment. We sought to evaluate the association between adverse events and their associations with premature discontinuation of dual antiplatelet therapy (DAPT). Methods: We enrolled East Asian patients presented with acute coronary syndrome who took DAPT with 90-mg ticagrelor (n=270) or 75-mg clopidogrel (n=674). During 1-month treatment, antiplatelet effect was evaluated with the VerifyNow P2Y12 assay, and the occurrence of Bleeding Academic Research Consortium (BARC) bleeding and modified Medical Research Council (mMRC) dyspnea was assessed with the dedicated questionnaire. Results: During 1-month follow-up, patients on ticagrelor showed the higher risks of bleeding (any BARC type: 45.6% vs. 23.6%; odds ratio [OR], 2.71 and BARC 1 or 2 type: 45.2% vs. 22.1%; OR, 2.90, respectively) and dyspnea (26.3% vs. 13.6%; OR, 2.25) compared with those on clopidogrel. In a receiver-operating characteristics curve analysis to predict bleeding risk, ticagrelor showed a lower cutoff of low platelet reactivity (LPR) (P2Y12 reaction unit [PRU] ≤20) than clopidogrel (PRU ≤110). Early occurrence of bleeding episode was significantly associated with LPR phenotype (OR, 2.68), not type of P2Y12 inhibitor. In multivariate analysis, type of P2Y12 inhibitor (ticagrelor vs. clopidogrel: OR, 2.19) and bleeding episode (OR, 2.94) were independent predictors for dyspnea occurrence. During 1-year follow-up, DAPT with ticagrelor showed a higher risk of premature discontinuation compared to DAPT with clopidogrel (27.8% vs. 4.7%; adjusted HR, 8.84), which risk appeared frequent during the first month (14.4%) during DAPT with ticagrelor. Early occurrence of bleeding and dyspnea synergistically increased a risk of DAPT non-adherence, irrespective of type of P2Y12 inhibitor. Conclusions: This analysis is the first evidence to show the different cutoff of low platelet reactivity during the reversible (ticagrelor) versus irreversible P2Y12 inhibitor (clopidogrel). Early occurrence of bleeding and dyspnea is very common during standard-dose ticagrelor treatment in East Asian patients, which show a close association with premature DAPT discontinuation.